Recent Advances in the Analysis of GDI and Diesel Fuel Injector Deposits. (15th July 2020) - Edney, Max K.; Barker, Jim; Reid, Jacqueline; Scurr, David J.; Snape, Colin E.
Highlights: Characterisation of GDI fuel deposits is an emerging field. Diesel deposits are layered materials with ranging structural order. Various analytical techniques have been used to study both deposits. MS techniques show promise for full characterisation. ToF-SIMS can analyse deposit layering but has a low mass resolution. Abstract: Formation of insoluble fuel deposits in external and internal parts of fuel injectors is a major issue globally for diesel and, more recently, gasoline direct injection (GDI) based engines. Deposit formation reduces fuel economy and increases emissions of almost every type of pollutant. Many potential causes exist such as general contamination, injector operating condition and the fuel composition. It is expected that as we move toward increased injection pressures to meet new emission targets, the occurrence and severity of deposits will increase. It is widely accepted that a necessary step to mitigating deposit formation is to understand their chemistry and structure to gain a deeper understanding into the formation mechanism. An array of analytical techniques have been applied for this endeavour to afford chemical, topographical and structural information on diesel deposits. This has extended into GDI deposits more recently. This literature review summarises the findings from studies into characterisation of both types of deposits and proposes that further work is required. Emphasis is also placed on the type of information offered by each analytical technique to aid researchers working in this field.